1991
DOI: 10.1063/1.461243
|View full text |Cite
|
Sign up to set email alerts
|

Bond-specific chemistry: OD:OH product ratios for the reactions H+HOD(100) and H+HOD(001)

Abstract: From laser-induced fluorescence measurements, the OD:OH product branching ratio is determined to be greater than 25:1 for the reaction H+HOD(001) and less than 1:8 for the reaction H+HOD(100). Fast H atoms are generated by the photolysis of HI at 266 nm and the HOD is excited to a specific vibronic state using an optical parametric oscillator. Here HOD(001) and HOD(100) correspond to O–H and O–D local-mode stretch fundamentals, respectively. Within our signal-to-noise level, reaction occurs exclusively with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
115
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 233 publications
(124 citation statements)
references
References 11 publications
8
115
0
1
Order By: Relevance
“…However, in the case of K = 0, the tumbling rotation may steer the reactants into a reactive orientation, thereby increasing the reactivity. Similar qualitative results were found recently for Cl + CHD 3 (v 1 = 1, JK), albeit the rotational enhancement factors are significantly larger for Cl + CHD 3 . 22 For example, JK = 50 and 55 enhance the Cl + CHD 3 reaction by factors of 5.3 and 2.5, respectively, 22 whereas the corresponding enhancement factors of O( 3 P) + CHD 3 are only 1.4(1.3) and 0.9(1.0).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…However, in the case of K = 0, the tumbling rotation may steer the reactants into a reactive orientation, thereby increasing the reactivity. Similar qualitative results were found recently for Cl + CHD 3 (v 1 = 1, JK), albeit the rotational enhancement factors are significantly larger for Cl + CHD 3 . 22 For example, JK = 50 and 55 enhance the Cl + CHD 3 reaction by factors of 5.3 and 2.5, respectively, 22 whereas the corresponding enhancement factors of O( 3 P) + CHD 3 are only 1.4(1.3) and 0.9(1.0).…”
Section: Resultssupporting
confidence: 90%
“…However, for K = 0 a clear J-dependence is seen, where the attack angle distributions shift from front-side attack to side-on attack orientations. For the JK = 80 state the reactivity is even larger at α = 90°than at α = 0°a nd significant reactivity is found when the O atom initially approaches the back side of CHD 3 . This side-on−back-side shift with increasing J is even more pronounced at lower E coll as seen by comparing the α distributions at 6.0 and 8.0 kcal/mol ( Figure 5.).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In this experimental study, the H atoms were generated with a microwave discharge, and the HOD molecule was prepared in a selected overtone stretch by laser irradiation in the visible wavelengths. Zare and co-workers (7) showed that the product-branching ratio selectivity was reduced but still survived for reactions of fast H atoms with HOD prepared in either the H-OD or HO-D stretching fundamental. Here, fast H atoms were generated by photolysis of HI, and the HOD stetching fundamental was excited by laser irradiation in the infrared.…”
Section: Mode-selective Chemistrymentioning
confidence: 99%
“…Furthermore, reaction dynamics theory can now provide detailed predictions with an accuracy that can rival experiment on simple reactions in the gas phase (7), and the theory has been extended, albeit more approximately, to more complex problems such as reactions of polyatomic molecules (8) and reactions on solid surfaces (9) and in solution (10).…”
Section: Quantum Theory Of Chemicalmentioning
confidence: 99%